Design and Building Information System of Raw Material Planning and Production Using Material Requirement Planning Method at Furniture Company - Daniel F. Kale; Henry Bambang Setyawan; Erwin Sutomo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
In fulfilling orders for subscriptions , companies must improve performance in terms of planning. So far the problem in CV. Azaria Abadi Permai is planning needs raw materials and production is still in expected and done manually by the passage production planning inventory control. In this case often happens miscalculation planning raw needs an impact on exactly the number and availability of the raw materials that it production process.                    Solution proposed for the completion of the problems in the top is using methods Material Requirement Planning. This method aims to count the needs of raw materials and the arrival buy raw materials used the results of the evaluation of three lot sizing the technique, Lot for Lot, Economic Order Quantity, and Period Order Quantity.                    The result of this research is able to analyze method lot sizing namely, Lot for Lot, Economic Order Quantity, Period Order Quantity and then to choose the cost of inventori the most economical in each this method.